2021
DOI: 10.2147/bctt.s231298
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Eribulin Mesylate in the Treatment of Breast Cancer: A Chinese Perspective

Abstract: Eribulin mesylate, a synthetic derivative of the anti-mitotic agent halichondrin B, has a unique tubulin-based mechanism of action that is distinct from other anti-microtubule agents including taxanes and vinca alkaloids. Consistent with this unique activity, eribulin has shown clinical efficacy in patients with metastatic breast cancer (MBC) that progressed following prior taxane and anthracycline therapy. The evidence presented in this review indicates that eribulin represents a treatment option for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Manageable adverse events were common in patients receiving both treatments, except for peripheral neuropathy observed in the eribulin treatment group, which resulted in the discontinuation of treatment in 5% (of 503 patients) of the patients [ 115 , 116 ]. EM was initially approved for patients with HER2-negative metastatic breast cancer, but it was also shown to lead to an effective clinical outcome for HER2-positive patients, indicating a broader use of the drug in the future [ 111 , 117 ].…”
Section: Marine Bioactive Compounds Available On the Marketmentioning
confidence: 99%
“…Manageable adverse events were common in patients receiving both treatments, except for peripheral neuropathy observed in the eribulin treatment group, which resulted in the discontinuation of treatment in 5% (of 503 patients) of the patients [ 115 , 116 ]. EM was initially approved for patients with HER2-negative metastatic breast cancer, but it was also shown to lead to an effective clinical outcome for HER2-positive patients, indicating a broader use of the drug in the future [ 111 , 117 ].…”
Section: Marine Bioactive Compounds Available On the Marketmentioning
confidence: 99%
“…Extracts from Haliclona (Soestella) mucosa (Griessinger, 1971), a Mediterranean sponge, was found to induce a cytotoxic effect and apoptosis in A375 human malignant melanoma cell line when used in combination with doxorubicin [41]. Halichondrin-B is a cytotoxin isolated from the sponge, Halichondria (Halichondria) okadai (Kadota, 1922), and it is known for its analogue, eribulin mesylate, which was approved by FDA in 2011 for the treatment of metastatic breast cancer [42]. However, Halichondrin-B demonstrated excellent preclinical activity in vivo by using different murine xenograft models of human cancer, such as colon cancer, glioblastoma, head and neck cancer, small-cell lung cancer and melanoma models [7,43].…”
Section: Discussionmentioning
confidence: 99%
“…It can be moderately well tolerated when administered orally once every day in daily doses of 1,250 mg-1,500 mg for 1-21 days. Gastrointestinal complications and skin rashes are the main toxicities observed in more than 20% of patients consuming Lapatinib (Yuan and Xu, 2021). It has been reported that Lapatinib is well accepted in patients who are resistant to Trastuzumab.…”
Section: Lapatinib Ditasylatementioning
confidence: 99%